Managing to Discriminate - Andiappan, Palaniappan (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "Managing to Discriminate," by David L. Collinson, David Knights and Margaret Collinson.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Sex discrimination; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z